Penglibatan Rakyat Malaysia dalam Ekstremisme Agama dan Langkah-Langkah Deradikalisasi: Malaysian Involvement in Religious Extremisme and Deradicalization Measures - Mohd Nor, Mohd Roslan; Munir, Misnal; Pandin, Moses Glorino Rumambo; Ibrahim, Muhammad Khalis (Online Journal of Research in Islamic Studies, 2022)
Although religious extremist movement led by ISIS has shown deterioration in both its operations and strength, this never eradicate people’s fears on religious extremism in future. Hence, this paper aims to examine the ISIS movement in Malaysia from an ideological standpoint, its activities, as well as to offer suggestions for deradicalization measures in facing future religious extremism. This study is based on the documentation method by collecting and researching various sources related to the scope of the discussion. Ideologically, ISIS adhered to the Salafi Jihadi doctrine which strict in interpreting religion. Similar to other countries, there were a small number of Malaysians who directly involved with the ISIS struggle in many ways. To face the threats of religious extremism, several suggestions for deradicalization measures are presented through the role of government, educational institutions, religious institutions, and security forces. This paper argues that any form of religious extremism must be holistically eradicated so that the image of Islam and national peace can be maintained.